Chromosome aberrations in lymphocytes of patients undergoing radon spa therapy: An explorative mfish study - Paz, Nerea; Hartel, Carola; Nasonova, Elena; Donaubauer, Anna-Jasmina; Frey, Benjamin; Ritter, Sylvia (International Journal of Environmental Research and Public Health, 2021)
In the present exploratory study, we aim to elucidate the action of radon in vivo and to assess the possible health risks. Chromosome aberrations were analyzed in lymphocytes of two patients (P1, P2) undergoing radon spa therapy in Bad Steben (Germany). Both patients, suffering from painful chronic degenerative disorders of the spine and joints, received nine baths (1.2 kBq/L at 34 °C) over a 3-week period. Chromosome aberrations were analyzed before and 6, 12 and 30 weeks after the start of therapy using the high-resolution multiplex fluorescence in situ hybridization (mFISH) technique. For comparison, the lymphocytes from two healthy donors (HD1, HD2) were examined. P1 had a higher baseline aberration frequency than P2 and both healthy donors (5.3 ± 1.3 vs. 2.0 ± 0.8, 1.4 ± 0.3 and 1.1 ± 0.1 aberrations/100 analyzed metaphases, respectively). Complex aberrations, biomarkers of densely ionizing radiation, were found in P1, P2 and HD1. Neither the aberration frequency nor the fraction of complex aberrations increased after radon spa treatment, i.e., based on biological dosimetry, no increased health risk was found. It is worth noting that a detailed breakpoint analysis revealed potentially clonal aberrations in both patients. Altogether, our data show pronounced inter-individual differences with respect to the number and types of aberrations, complicating the risk analysis of low doses such as those received during radon therapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Clonal aberrations; Complex aberrations; MFISH; Radon; T-cell receptor genes